Fra glosse medievali e dialetti moderni: riconsiderando le glosse romanze del codice criptense Gr. Z. α. IV (Atti del Sodalizio Glottologico Milanese, 2019)
Again on some ancient Romance glosses (from Southern Italy) in Greek alphabet. The glosses (Romance interlinear translation of difficult ancient Greek words in a Greek grammatical text) are of uncertain dating (XIII-XIV, perhaps XV, centuries), sometimes of uncertain interpretation (e.g.: what does a Romance sequence such as λουτζεσινερι, gloss n. 24, mean?), in any case of uncertain origin. In fact their very complex linguistic facies gathers many different elements (phonetic features, lexical items…), which can refer from time to time to Sicily, or to Calabria or to Salentine peninsula. New proposals about it. KEYWORDS: Greek, Romance, glosses, translation, transcription